Postnatal health of infants born to mothers with autoimmune diseases when treated with hydroxychloroquine - Matys, Viviana; Rizzo, Francesca; De Carolis, Maria Pia; Barresi, Salvatore; Serio, Anna Maria; Lanzone, Antonio; Garufi, Ester; De Carolis, Sara; Garufi, Cristina (Frontiers in Lupus, 2025)
This retrospective cohort study aimed to observe the postnatal health of infants born to mothers with systemic autoimmune rheumatic diseases treated with hydroxychloroquine (HCQ) during pregnancy. A total of 312 pregnancies of patients who suffered from different systemic autoimmune rheumatic diseases were considered. Pregnancy data were collected; a telephone follow-up questionnaire was successfully completed in 182 infants to detect the long-term pediatric outcome. The women who took hydroxychloroquine during pregnancy were defined as “HCQ group” and were compared to women who did not take hydroxychloroquine, “non-HCQ group”. A higher prevalence of women with multiple maternal diseases was detected in the HCQ group, in comparison to that of non-HCQ group (p=0.0015). Despite HCQ group consisting of more complicated maternal conditions, the obstetrical and neonatal outcomes were similar between the two groups. Regarding postnatal health, 40% of infants in HCQ group revealed no pathologies versus 25% of the children in non-HCQ group (p= 0.0368). The protective role of HCQ on infants should be further evaluated in prospective multicenter long-term studies.